2020
DOI: 10.5194/bg-17-851-2020
|View full text |Cite
|
Sign up to set email alerts
|

No nitrogen fixation in the Bay of Bengal?

Abstract: The Bay of Bengal (BoB) has long stood as a biogeochemical enigma, with subsurface waters containing extremely low, but persistent, concentrations of oxygen in the nanomolar range which -for some, yet unconstrained, reason -are prevented from becoming anoxic. One reason for this may be the low productivity of the BoB waters due to nutrient limitation and the resulting lack of respiration of organic material at intermediate waters. Thus, the parameters determining primary production are key in understanding wha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 97 publications
7
49
1
Order By: Relevance
“…The N 2 fixation rates observed in our study are higher than the recently reported rates in the Bay for January 2014 (Löscher et al 2020) where the rates at DCM were below detection limit though they found the clusters of N 2 fixing microbes. Löscher et al (2020) targeted oxygen minimum zones for heterotrophic N 2 fixation rates, while most of the N 2 fixation occurs in the surface waters. Carbon uptake rates in their study ranged between 286-1855 nmol C l −1 d −1 at the depth of DCM whereas in our study, it varied from 1.4 to 282.2 nM C hr −1 (or 17 to 3386 nM C d −1 ) in the Sunlit layer of the Bay.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…The N 2 fixation rates observed in our study are higher than the recently reported rates in the Bay for January 2014 (Löscher et al 2020) where the rates at DCM were below detection limit though they found the clusters of N 2 fixing microbes. Löscher et al (2020) targeted oxygen minimum zones for heterotrophic N 2 fixation rates, while most of the N 2 fixation occurs in the surface waters. Carbon uptake rates in their study ranged between 286-1855 nmol C l −1 d −1 at the depth of DCM whereas in our study, it varied from 1.4 to 282.2 nM C hr −1 (or 17 to 3386 nM C d −1 ) in the Sunlit layer of the Bay.…”
Section: Discussioncontrasting
confidence: 92%
“…(more abundant) and unicellular diazotrophic cyanobacteria along with proteobacteria (mainly alpha-, beta-, and gamma-proteobacteria) with higher abundance in the equatorial region. During winter monsoon, Löscher et al (2020) observed Synechococcus and Trichodesmium with no evidence of unicellular diazotrophic cyanobacteria. Diatoms-associated diazotrophs have also been reported during summer monsoon for same sampling stations as ours (Bhaskar et al 2007).…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, in the BoB-OMZ has been reported less intense than the AS-OMZ (Paulmier, 2009) with DO concentrations still present in the nanomolar range (Bristow et al, 2017). Nitrogen loss has been described as rather insignificant and limited by substrate availability resulting from low organic matter supply by primary production (Bristow et al, 2017;Löscher et al, 2020). The sequence of electron acceptor utilization in such an environment, generally follow the thermodynamic energy yield (Froelich et al, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…13. Unfortunately, our model simulations differ most strongly in the Indian Ocean, for which no data exist in the MAREDAT database of Luo et al (2012). One of the problems we face regarding N 2 fixation is that our UVic simulations do not include benthic denitrification and hence miss the dominant oceanic fixed-N loss term (e.g.…”
Section: N 2 Fixation and Diazotrophsmentioning
confidence: 98%
“…Estimates of Chl (MODIS Aqua, level 3; https://oceancolor.gsfc.nasa.gov/l3/, last access: 11 November 2019; Hu et al, 2012), particulate organic carbon, and net primary and community production (POC, NPP, and NCP;Westberry et al, 2008;Li and Cassar, 2016) are based on satellite data. In situ N 2 -fixation data are from MARine Ecosystem biomass DATa (MAREDAT) (Luo et al, 2012). 3 , and PO 3− 4 concentrations.…”
Section: Parametermentioning
confidence: 99%